Prosa Calibre 38 : um estudo sobre a personagem Anísio na novela e no filme O Invasor - Guedes, Marcílio Borba (2010)
What basic differences distinguish literature from film as different kinds of art? Is the novel always better than the film? What can we gain or lose when a novel is adapted for the screen? Is the notion of fidelity important if we want a successful adaptation? Our aim in this work is to try to answer these questions, and in order to do that we have taken as our object the main character of the novel O Invasor, by Marçal Aquino, and of its filmic adaptation, by Beto Brant. Based on the study of this character, and focusing on relations of power (Foucault) we try to understand how the phenomenon of adaptation works as a process and industry activity , as well as show that both literature and cinema have subtle and specific ways of telling a story and that the dialogue between the two arts is something concrete.